1979
DOI: 10.1007/bf01221952
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan-induced alteration of insulin release, rubidium efflux and glucose metabolism in rat islets stimulated by various secretagogues

Abstract: Summary.Insulin release and 86Rb efflux were studied in perifused rat islets exposed in vitro to alloxan (2 mmol/1) for 5 min. At a low glucose concentration, alloxan transiently increased 86Rb efflux. Alloxan immediately and completely abolished the secretory response to glucose (15 mmol/1) and markedly delayed the reduction in 86Rb efflux normally produced by the sugar. 3-0-methylglucose (20 mmol/ 1) provided complete protection against the alteration of 86Rb efflux and partial protection against the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…3), indicating an inhibition of the release of insulin stored in granules in alloxan-treated mice. This agrees with the observation that alloxan inhibits glucose-induced insulin secretion ( Gunnarsson & Hellerstrom 1973, Henquin et al 1979. This inhibition is abolished by glucose in vitro (Tornita & Lacy 1972).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…3), indicating an inhibition of the release of insulin stored in granules in alloxan-treated mice. This agrees with the observation that alloxan inhibits glucose-induced insulin secretion ( Gunnarsson & Hellerstrom 1973, Henquin et al 1979. This inhibition is abolished by glucose in vitro (Tornita & Lacy 1972).…”
supporting
confidence: 90%
“…1975, Weaver et (11. 19781, or for an intracellular action, besides plasma membrane effects (Henquin et al 1979). Autoradiography has revealed that mouse islets accumulate alloxan Wammurstrom et al 1967).…”
mentioning
confidence: 99%
“…The diabetes-inducing substance alloxan [120,121] mainly acts via the liberation of H 2 O 2 [122,123]. Consequently, alloxan has very similar effects on islets as H 2 O 2 with respect to V m , K ATP current and [Ca 2+ ] c [74].…”
Section: Ros/rns and Ion Channelsmentioning
confidence: 99%
“…/ /<'-... tent protect glucose-induced insulin secretion [66] and pancreatic B cell glucokinase (S.Lenzen, unpublished observation) against alloxan inhibition. Insulin secretion, in response to other fuel insulin secretagogues such as leucine and 2-ketoisocaproate and the hypoglycaemic sulfonylurea drugs, which are not recognised as insulin secretagogues by the pancreatic B cell through interaction with the glucokinase [41, 67, 681, is not immediately and completely inhibited by alloxan [69,70]. 8.…”
Section: Mechanism Of Action Of Alloxan On the Pancreatic B Cellmentioning
confidence: 99%